The trade-off between absorptive capacity and appropriability of the returns to innovation effort - Frank Crowley; Declan Jordan (University College Cork, Spatial and Regional Economic Research Centre (SRERC), 2018)
A key concept in the economics of innovation is the 'public good' nature of knowledge. This generates a tension between incentivizing knowledge production by allowing knowledge creators appropriate the economic benefits and encouraging its diffusion to enhance the social return to knowledge creation. Where firms operate in localities that are characterized by greater entrepreneurship, there may be lower incentives to engage in research and development. This would result from a higher risk of knowledge spillovers to local start-ups and/or that employees may exploit new knowledge in spin-out firms. It has also been suggested in the literature that greater local entrepreneurial activity may lower profits for incumbent firms, through greater competition and/or the leakage of commercially valuable new knowledge. This paper presents a novel conceptual perspective on this tension and empirically tests it. Using Swedish firmlevel data and county-level data on new start-ups, this paper estimates the effect on R&D activity of local rates of business start-ups. It finds that greater numbers of new start-ups in a metropolitan area reduces firm-level R&D expenditure. However, this relationship is not linear, so that at higher levels of new firm formation in a region, firm-level R&D expenditure falls at a diminishing rate. This suggests that the effect of local entrepreneurship on a business' R&D decisions is conditioned by the extent of that entrepreneurship.
Keywords: R11; O33; O31; 330; Innovation; entrepreneurship; absorptive capacity; knowledge spillovers